Epidemiologic Characteristics, Prognostic Factors, and Treatment Outcomes in Primary Central Nervous System Lymphoma: A SEER-Based Study - Tang, Dongsheng; Chen, Yue; Shi, Yuye; Tao, Hong; Tao, Shandong; Zhang, Quan’e; Ding, Banghe; He, Zhengmei; Yu, Liang; Wang, Chunling (Frontiers in Oncology, 2022)
Objective This study was conducted in order to study the clinical characteristics, prognostic factors, and treatment outcomes in patients with primary central nervous system lymphoma (PCNSL). Materials and Methods The data of a total of 5,166 PCNSL patients diagnosed between 2000 and 2018 from the Surveillance, Epidemiology, and End Results (SEER) database were obtained. Results The mean age was 63.1 ± 14.9 years, with a male to female ratio of 1.1:1.0. The most common histologic subtype was diffuse large B-cell lymphoma (DLBCL) (84.6%). The 1-, 3-, and 5-year overall survival (OS) rates were 50.1%, 36.0%, and 27.2%, respectively, and the corresponding disease-specific survival (DSS) rates were 54.4%, 41.3%, and 33.5%, respectively. Multivariate analysis with Cox regression showed that race, sex, age, marital status, surgical resection, and chemotherapy were independent prognostic factors for OS and DSS, but radiotherapy was only for OS. Nomograms specially for DLBCL were established to predict the possibility of OS and DSS. The concordance index (C-index) values of OS and DSS were 0.704 (95% CI 0.687–0.721) and 0.698 (95% CI 0.679–0.717), suggesting the high discrimination ability of the nomograms. Conclusion Surgical resection and/or chemotherapy was favorably associated with better OS and DSS. However, radiotherapy was not beneficial for OS and DSS in the long term. A new predictive nomogram and a web-based survival rate calculator we developed showed favorable applicability and accuracy to predict the long-term OS for DLBCL patients specifically.